A Study Of The Long-Term Equilibrium Relationship Between Education And Human Development Indicators In Syria - أحمد طالب; نجار كمال (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The Aim Of The Research Is To Use The Method Of Co-Integration Between The Two Indicators Of Education And Human Development In Syria By Applying The Johansson Method And The Error Correction Model To Find Out If There Is A Long-Term Equilibrium Relationship Between The Two Indicators? The Most Important Results Of The Study Were: There Is A Long-Term Equilibrium Relationship Between The Education And Human Development Indicators, And Based On The Granger Causal Test, It Was Found That There Is A One-Way Causal Relationship From The Education Indicator To The Human Development Indicator. According To The Error Correction Model, The Education Indicator Explains 4% Of The Changes In The Human Development Index In The Long Run. That Is, The Value Of The Education Indicator Is Adjusted Towards Its Equilibrium Value In Each Time Period With A Percentage Of The Remaining Imbalance From The Previous Time Period (The Previous Year) Equivalent To 4%.